A lateral global buckling failure envelope for a high temperature and high pressure (HT/HP) submarine pipeline. (June 2015) - Hong, Zhaohui; Liu, Run; Liu, Wenbin; Yan, Shuwang
Highlights: Propose the lateral global buckling failure envelope for post-buckling pipeline. Estimate the calculation equation for the failure envelope based on sensitivity analysis of influence factors in pipeline lateral global buckling. Suggest an easier, more efficient assessment method for a post-buckling pipeline. Abstract: Submarine pipelines are the primary component of an offshore oil transportation system. Under operating conditions, a pipeline is subjected to high temperatures and pressures to improve oil mobility. As a result, additional stress accumulates in pipeline sections, which causes global buckling. For an exposed deep-water pipeline, lateral buckling is the major form of this global buckling. Large lateral displacement causes a very high bending moment which may lead to a local buckling failure in the pipe cross-section. This paper proposes a lateral global buckling failure envelope for deep-water HT/HP pipelines using a numerical simulation analysis. It analyzes the factors influencing the envelope, including the thickness t, diameter D, soil resistance coefficient μ, calculating length L f, imperfection length L and imperfection amplitude V . Equations to calculate the failure envelope are established to make future post-buckling pipeline failure assessment more convenient. The results show that (1) the limit pressure difference p max (the failure pressure difference for a post-buckling pipeline when it suffers no difference in temperature) is usually below the burst pressure difference p b (which is the largest pressure difference a pipeline can bear and is determined from the strength and sectional dimensions of the pipeline) and is approximately 0.62–0.75 times the value of p b and (2) thickness t has little influence on the normalized envelopes, but affects p max . The diameter D, soil resistance coefficient μ, and calculating length L f influence the maximum failure temperature difference T max (the failure temperature difference for a pipeline suffering no pressure difference). The diameter D also significantly affects the form of the normalized envelope.